Modal analysis of pipe joint spiral wound gasket - Nabil Fahmi, Mohtar (2010)
This project report deals with dynamic behaviour of spiral wound gasket using theoretical and experimental analysis method. This project report is to study the dynamic properties and behaviour of spiral wound gasket by using modal analysis and compare with the finite element analysis. The structural three-dimensional solid modelling of spiral wound gasket was developed using the SOLIDWORK drawing software. The finite element analysis was then performed using ALGOR (FEA). The finite element model of the components was analyzed using the linear modal analysis approach. Finally, the experimental modal analysis was performed using Impact Hammer Testing method. The natural frequency of the mode shape is determined and comparative study was done from both method results. The comparison between natural frequencies of finite element modelling and model testing shows the closeness of the results. From the results, the percentage error had been determined and the limitation in the natural frequency of the spiral wound gasket is observed.